Rubber Farmers' Activities in Maruta Anjir Serapat Village - Arini, Arini; Sari, Raihanah; Mutiani, Mutiani; Syarifuddin, Syarifuddin; Nur'aini, Fatwa (Program Studi Pendidikan IPS, 2026)
This study aims to describe the activities of rubber farmers and the obstacles they face in the tapping process. The research location was in Maruta Anjir Serapat Village, East Kapuas District, Kapuas Regency, Central Kalimantan Province. The study used a qualitative descriptive approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the main activities of farmers include tapping rubber at night, collecting sap, processing, and selling to local collectors. These activities are the main source of income for farmers. However, they face several obstacles such as unpredictable weather, especially during the rainy season, which disrupts the tapping process and reduces sap yield. In addition, fluctuating rubber prices cause farmers' incomes to be unstable. Damaged road infrastructure also hinders access to plantations and distribution of produce. Nevertheless, farmers remain persistent in their rubber farming activities. This study concludes that support from various parties, especially the government, is urgently needed. Recommended forms of support include road repairs, subsidies for fertilizers and production tools, guidance, and improved market access to enhance farmers' productivity and welfare in a sustainable manner.